An evaluation of toy quality for increasing self‐control in typically developing preschool children. Issue 3 (9th June 2016) - Juanico, Jessica F.; Dozier, Claudia L.; Payne, Steven W.; Ackerlund Brandt, Julie A.; Jowett Hirst, Erica S.
Abstract : Children often make impulsive choices, and previous research has shown that access to activities during the delay may enhance self‐control (e.g., Newquist, Dozier, & Neidert, 2012). The purpose of the current study was to extend the results of Newquist et al. (2012) by comparing the effects of access to low‐preference, moderate‐preference, and high‐preference toys during delays. Results showed that (a) all toys increased self‐control for 2 participants when toys were available for all choice options and (b) high‐preference toys (and sometimes moderate‐preference toys) increased self‐control for 3 participants when the toys were available only for large delayed choices. Abstract : Podcast